Synthesis, characterization and in vitro biological studies of novel Nitrilo derivatives of N-substituted phenyl piperazine - AL-Mashkor , Idries (University of Thi-Qar Journal of Science, 2011)
Nitrilo derivatives of N-alkyl and N-aryl phenyl piperazine have been synthesized andscreened for antibacterial and antifungal activities. All the synthesized compounds showed theantibacterial activity against pathogenic strains of Staphylococcus aureus (MTCCB 737),Pseudomonas aeruginosa (MTCCB 741),Streptomyces epidermidis (MTCCB 1824) andEscherichia coli(MTCCB 1652) and antifungal activity against pathogenic strains ofAspergillus fumigatus (ITCC 4517), Aspergillus flavus (ITCC 5192) and Aspergillus niger(ITCC 5405). All compounds showed mild to moderate antimicrobial activity. However,compounds 3c, 4a and 6 showed potent antibacterial activity against pathogenic strains usedin the study. Compounds 3a, 3b, 4b, and 4d showed mild to moderate antifungal activityagainst Aspergillus pathogenic strains.